The divided states of America : why federalism doesn't work - Kettl, Donald F. (Princeton University Press, 2020)
"As James Madison led America's effort to write its Constitution, he made two great inventions-the separation of powers and federalism. The first is more famous, but the second was most essential because, without federalism, there could have been no United States of America. Federalism has always been about setting the balance of power between the federal government and the states-and that's revolved around deciding just how much inequality the country was prepared to accept in exchange for making piece among often-warring states. Through the course of its history, the country has moved through a series of phases, some of which put more power into the hands of the federal government, and some rested more power in the states. Sometimes this rebalancing led to armed conflict. The Civil War, of course, almost split the nation permanently apart. And sometimes it led to political battles. By the end of the 1960s, however, the country seemed to have settled into a quiet agreement that inequality was a prime national concern, that the federal government had the responsibility for addressing it through its own policies, and that the states would serve as administrative agents of that policy. But as that agreement seemed set, federalism drifted from national debate, just as the states began using their administrative role to push in very different directions. The result has been a rising tide of inequality, with the great invention that helped create the nation increasingly driving it apart"--